Shark attacks on offshore streamer cables. (March 2020) - Rølvåg, Terje; Hagen, Axel B.; Hagen, Tarald B.
Abstract: In the search for new subsea oil fields, geologists use vessels to tow streamer cables, which collects seismic data. This activity attracts bull sharks to the magnetic streamer fields causing shark attacks and hence losses and delays. This paper discusses how shark attacks on streamer cables can be modelled and simulated in cable design and optimization processes. In order to generate a representative simulation model, a large and authentic bull shark jaw was 3D-scanned. The shark jaw was converted to a CAD-model utilizing reverse engineering applications. Numerical models of the streamer cables, capturing the response with respect to friction properties and failure criteria's, were benchmarked using quasi-static compression tests. Additionally, dynamic bite and impact simulations replicating the shark attack on streamer cables have been conducted. The physical compression tests and simulations show that the streamer cable FE-models are valid. The results indicate that a shark bite can be sufficient to critically damage the cable, but the bite resilience of the streamer cable is strongly correlated to the shark speed upon impact.